1978
DOI: 10.1002/anie.197808481
|View full text |Cite
|
Sign up to set email alerts
|

Existence of a New C6H6 Isomer: Tricyclo[3.1.0.02,6]hex‐1(6)‐ene

Abstract: “Isobenzvalene” (1), a very highly strained molecule, has now been trapped in the form of the Diels‐Alder adduct (2) with anthracene. The structure of (2) is also unusual: C‐11 and C‐16 are both located outside the tetrahedron formed by their four substituents (“inverted tetrahedron”).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…An unusual rearrangement was observed in the halomethyl series described above.7,14 Thus, no difficulty was experienced in preparing dibromide 27 from did 26, but when carbon tetrachloride was used in place of carbon tetrabromide in an analogous reaction, furan 41 was isolated and only small amounts of dichloride 12a were detected. A tentative mechanism has been suggested whereby intramolecular displacement of the first-formed oxaphosphonium ion intermediate 42 by the adjacent hydroxyl group leads to the [3.1.1]propellane intermediate 43.19 This tricyclopentanone is highly strained and undergoes a bicyclobutane to butadiene isomerization reaction.20 Since the product 44 of that change is a cyclopentadienone, it is also unstable and escapes by tautomerization to the final furan product 41. The structure of furan 41 was confirmed by independent synthesis of an authentic sample.7 A bicyclobutane to butadiene transformation also occurs in an iodine-catalyzed reaction of the dimethyltricyclo[2.1.0.02,5]pentanone 6a.…”
Section: Rearrangements and Isomerizationsmentioning
confidence: 99%
“…An unusual rearrangement was observed in the halomethyl series described above.7,14 Thus, no difficulty was experienced in preparing dibromide 27 from did 26, but when carbon tetrachloride was used in place of carbon tetrabromide in an analogous reaction, furan 41 was isolated and only small amounts of dichloride 12a were detected. A tentative mechanism has been suggested whereby intramolecular displacement of the first-formed oxaphosphonium ion intermediate 42 by the adjacent hydroxyl group leads to the [3.1.1]propellane intermediate 43.19 This tricyclopentanone is highly strained and undergoes a bicyclobutane to butadiene isomerization reaction.20 Since the product 44 of that change is a cyclopentadienone, it is also unstable and escapes by tautomerization to the final furan product 41. The structure of furan 41 was confirmed by independent synthesis of an authentic sample.7 A bicyclobutane to butadiene transformation also occurs in an iodine-catalyzed reaction of the dimethyltricyclo[2.1.0.02,5]pentanone 6a.…”
Section: Rearrangements and Isomerizationsmentioning
confidence: 99%
“…This species is referred to frequently as mbenzyne in analogy with o-benzyne. Although evidence for the diradical has been presented in only one instance for simple benzene derivatives,43 there is a considerable body of evidence for the isomeric bicyclo[3.1.0]hexa-1,3,5-triene form (68). Numerous theoretical calculations at various levels of sophistication have focused on the dehydrobenzenes.…”
Section: Ch Mementioning
confidence: 99%
“…48 The singlet bicyclohexatriene was predicted to be the ground state with the optimum singlet structure best described as a reasonance-delocalized bicyclo[3.1.0]hexatriene with a bridging bond of 1.5 A. In a similar study of the dehydrobenzenes, Dewar and co-workers concluded that 68 should exist as a singlet species containing a long bridging a bond between Cx and C5.49 Noell and Newton also calculated 68 to exist in the singlet ground state.50 Whereas Washburn found no energy barrier for the collapse of diradical 67 to bicyclic 68, Dewar calculated 68 to be separated from 67 by a barrier of 9 kcal/mol.49b As might be expected, theoretical treatment of 68 predicts w polarization analogous to that of an azulenoid hydrocarbon.…”
Section: Ch Mementioning
confidence: 99%
“…0 2,7 . 0 3,7 ]dodeca-9,11-diene (Szeimies-Seebach, Harnisch, Szeimies, Van Meerssche, Germain & Declercq, 1978). This structure which was given the code name MUNICH1, has space group C2 with formula C20H16 and Z = 8.…”
Section: Some Applications Of Magexmentioning
confidence: 99%